O fetichismo: para uma crítica radical do trabalho abstrato-concreto. Investigações sobre a teoria do valor de Marx - Silva Júnior, José Valdo Barros (2010)
The aim of this dissertation is to strike a radical critique at abstract-concrete labor as a fetishist principle that constitutes the modern commodity-producing society. All this from the point of view of Karl Marx’s theory of value. Firstly, it scrutinizes the structure of commodity as a concrete social unit that carries inherently a double determination, which means it is both a use-value and a value. The twofold nature of commodity is derived from the twofold nature of labor, while at same time abstract and concrete. There is an antagonistic relation both within the commodity and the labor, however, the value is imposed on the use-value of destructive form. On the other hand, the abstract-labor is imposed also on its destructively way, which is named the concrete-labor. This antagonism is characterized by a negative logic, which tends to generate increasing unsustainable contradictions. The core of these contradictions lies the fact that the whole commodity-producing social reality of modernity is based on a real social abstraction: the value-being. This being is originally constituted by the abstract-labor as social substance. Secondly, it determines that the negative logic which permeates the structure of commodity has a fetish-like character. This character becomes the socially produced objects by abstract-concrete labor in things at same time sensible and supersensible. The fetish-like character of commodities is derived from the twofold nature of labor that produced them. The fetishism is an absurd social mechanism that engenders the reality of society as if it was dominated by autonomous things, which have anonymous powers against individuals themselves who produced them. The social mechanism of fetishization of reality is formed by habit of social relations of production. This habit makes the commodities to appear having a property of value-being as something natural. But this property is merely socially constituted by labor. The strongly consolidation of this mechanism occurs because it is characterized by three dimensions: an objective (reality), a subjective (thoughts) and an intersubjective dimension. The unity of these three dimensions constitutes the commodity-producing modern society as a negative totality, since it is determined by a priori matrix that characterizes fetishistically to the act, speaks and fells of all its members through an impersonal power. Thirdly, it investigates the historical and logical horizon in which the abstract-concrete labor is limited: merely the commodity-producing modern system. This limitation will be complemented with the Marx’s theory of final crisis of capitalism. This theory turns out to characterize the labor as a historically determined category and so it belongs only to commodity-producing modern system. It is not therefore an ontological principle that determines the man’s essence as a social being founded by and through labor, nor a transhistorical principle belonging to all forms of sociability. Finally, it concludes according to contend, form and matter of the commodity-producing modern society that history is the history of fetishists relations and not the history of class struggles.